Effective Individual and Professional Features in Clinical Training from the Viewpoint of Students, Professors, and Speech Therapists - Hossein Gerivani; Hossein Mobaraki; Mohammad Kamali; Ali Ghorbani (Zanjan University of Medical Sciences and Health Services, 2018)
Background and Objective: One of the goals of clinical education is providing students with sufficient opportunity to develop the necessary professional competences, which requires constant assessment of the existing situation, recognition of strengths and correction of weaknesses. This study aimed to evaluate and identify the individual and professional features effective in clinical education in the field of speech therapy. Materials and Methods: This study, based on the paradigm of qualitative content analysis, was conducted on 13 students, 6 instructors and 6 speech therapists, who were selected through purposive sampling. Data were collected using in-depth and semi-structured interviews and group discussions. In addition, data analysis was carried out applying the Colaizzi's method. Results: Individual and professional features of individuals involved in clinical practice were recognized as factors affecting the quality of clinical education in speech therapy. Leaning motivation and background knowledge were recognized as effective features related to students, whereas feedback provision and clinical experience were identified for clinical instructors. Moreover, accountability of clients was an effective factor in this regard. Conclusion: According to the results of the study, individual and professional features can affect the quality of clinical education in speech therapy. Mostly, the role of clinical instructors was emphasized by interviewees, who recognized the motivation, experience and knowledge of clinical instructors as the important factors for successful clinical education.